MEMAHAMI PENTINGNYA PERAN RUANG BERSAMA DALAM MEMPERKUAT KETERIKATAN TEMPAT DI RUMAH SUSUN SEDERHANA - Neni Nurul Rosalina (Akademi Seni dan Desain Indonesia Surakarta, 2023)
Place attachment is a concept that has gained attention in recent years due to its potential in understanding the relationship between individuals and the built environment. It refers to the emotional bond or connection that people develop with a place, and is often influenced by various factors. In the context of public rental housing in Indonesia, the issue of place attachment is particularly relevant, as many residents face challenges in developing a sense of attachment and belonging to their homes. However, recent research suggests that the provision of high-quality public spaces in public housingcan play a critical role in strengthening residents' sense of place attachment, as well as promotingenvironmental behavior and community participation. Despite the potential benefits of public spaces inpublic housing, there is a need for further research to understand how these spaces can be designed andmanaged to effectively promote place attachment. Qualitative method used in this study to allow for amore nuanced and comprehensive understanding of the relationship between public spaces, placeattachment, and related outcomes, which could inform future policy and practice in the design andmanagement of public housing environments. Results show that accessibility, safety, and the presenceof natural elements in public spaces, such as trees and greenery, was positively associated withresidents' sense of place attachment. The improvement and maintenance of public spaces would promotepositive outcomes for residentsKeywords: place attachment, public spaces, public housin